Penerapan Pembelajaran Interaktif dalam Program SSN untuk Meningkatkan Pemahaman Surah Pendek dan Tajwid Siswa SD - Siti Mutthola’ah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Qur’anic learning at the elementary school level plays an important role in developing students’ Qur’anic literacy, including reading skills, memorization, and understanding of tajweed rules. One initiative supporting this goal is the Sekolah Sisan Ngaji (SSN) program, introduced by the Blora Regency Government to strengthen Qur’anic education in elementary and junior high schools. This study aims to analyze the effectiveness of interactive learning methods within the SSN program in improving students’ understanding of short surahs and tajweed at SD Islam Plus Al Mukhtariyyah. This study employed a qualitative descriptive approach focusing on classroom learning activities. The participants were 19 fourth-grade students. The learning process was conducted in three meetings, each lasting 40 minutes, using Surah Az-Zalzalah as the learning material, including its meaning and tajweed application. Interactive learning methods included question-and-answer sessions, teacher-guided recitation review (murojaah), recitation demonstrations, audiovisual media, quizzes, and direct feedback. Data were collected through observation, documentation, and learning evaluation. The findings revealed increased student participation, with 16 students becoming more active in learning activities and 15 students showing improvement in reading fluency and tajweed application.